Chrysostom on hunger and famine - Stander, Hennie (HTS teologiese studies, 2011)
This article looked at hunger and famine in Chrysostom’s time. It has always been tragic and ironic that hunger should exist in a world of plenty. This topic has been discussed from an economic, social, theological, philosophical, medical, humanitarian and exegetical perspective. Chrysostom’s statements on this issue are studied, but our concern is only involuntary hunger, whilst voluntary forms of self-denial are being excluded. An attempt is made to define a social construct of poverty and hunger in Chrysostom’s world.